Symbolic Meaning in the Commemoration Ceremony of Sultan Hamengku Buwono X Coronation in COVID-19 Pandemic - Nur'aini, Fitria; Sumarwati, Sumarwati; Sulaksono, Djoko (Bina Nusantara University, 2022)
The research aimed to (1) describe the procession and ubarampe offerings in the commemoration ceremony of Sultan Hamengku Buwono X’s coronation during the COVID-19 pandemic, and (2) analyze the symbolic meaning of it. The research applied a qualitative research that used an ethnographic approach. Data collection techniques used were passive participant observation techniques and in-depth interviews with abdi dalem (courtier) of Yogyakarta palace and cultural experts. So, the selection of research subjects used the snowball sampling technique. The data obtained were validated by the source triangulation method, and it was then analyzed using the Spradley model research method, which included domain analysis, taxonomic analysis, compensatory analysis, and analysis of cultural themes. The research result show that (1) the procession of the commemoration of the coronation of Sultan Hamengku Buwono X consists of a series of ceremonies, including ngebluk, ngapem, sugengan, and labuhan. The ceremony is organized well during the COVID-19 pandemic by wearing a mask when carrying out daily activities, washing hands often, especially after outdoor activities, social distancing, avoiding crowds, and restricting mobilization and interaction, (2) the symbolic meaning of the procession and ubarampe offerings Sultan Hamengku Buwono X is asking God for the safety and welfare of the Sultan and his family in particular and Yogyakarta people in general.